In vitro Antibacterial Activity of Combretum edwardsii, Combretum krausii, and Maytenus nemorosa and Their Synergistic Effects in Combination with Antibiotics - Chukwujekwu, Jude C.; van Staden, Johannes (Frontiers in Pharmacology, 2016)
Abstract The study investigated the antibacterial activity of crude extracts of Combretum edwardsii, Combretum krausii and Maytenus nemorosa as well as their interactions with selected antibiotics against drug resistant bacterial strains. Using the rapid p-iodonitrotetrazolium chloride colorimetric assay, minimum inhibitory concentration values of plant extracts and antibiotics were determined. The interactions of plant extracts and antibiotics were studied using a checkerboard method. The MICs of the plant extracts and antibiotics were in the range of 0.037 - 6.25 mg/ml and 0.001 - 2.5 mg/ml respectively. The plant fractions tested in the present study displayed varying levels of antibacterial activity depending on the bacterial strains. Generally, S. aureus was the most susceptible of the three strains of bacteria while the other two beta-lactamase producing Gram-negative bacteria were the most resistant. The hexane leaf extract of Maytenus nemorosa was the most active (MIC = 37 µg/ml) against Staphylococcus aureus. Ethyl acetate leaf extract of Combretum krausii was the most active against Klebsiella pneumoniae and ethyl acetate leaf extract of Combretum edwardsii was the most active against Escherichia coli. Synergistic interactions were detected in 13 % of the combinations against Escherichia coli, 27 % of the combinations against Klebsiella pneumoniae and 80 % of the combinations against Staphylococcus aureus. The few synergistic interactions observed in the present study suggest that the crude extracts of the leaves of Maytenus nemorosa, Combretum edwardsii and Combretum krausii could be potential sources of broad spectrum antibiotic resistance modifying compounds.